Ways to Hold National Action Games with Kindergarten Children - Kadirov Shokhrukh Nematovich (International Journal on Orange Technologies, 2022)
In this article, the educator-organizer is familiar with these exercises, good knowledge of movement games, pedagogical principles in their organization (gradual, easy-difficult, simple to complex, familiar to unfamiliar, repetition, explanation, teaching new games, games completion, etc.) full compliance is highlighted.